The Approach of Literary Appreciation of Mahmoud Shaker and Muhammad Abi Musa: (Critical Reading) - AbdulShaheed, Sura Saleem (Al-Adab Journal, 2022)
This study deals with (The Approach of Literary Appreciation of Mahmoud Shaker and Muhammad Abi Musa - Critical Reading). By identifying the most prominent motives for heading for each of these two venerable sciences to this method, which almost differs from all literary, critical, and intellectual curricula that the university and scientific institutes dealt with by teaching, learning, and instructing students for a generation after a generation. The study also reveals the effect of Mahmoud Shaker’s approach on his students generally, and on Dr. Muhammad Abi Musa in particular, how they received that method, how they followed it in their books and writings, and what is the response of the university or the academic direction of that curriculum. In the light of this, the study faced literary and intellectual battles about the curriculum of Mahmoud Shaker and Muhammad Abi Musa. The students and writers divided between those who supported or rejected this curriculum. The memorable battle is of pre-Islamic poetry that developed and extended its roots to (Al-Mutanabbi)'s book written by Mahmoud Shaker. In which he responded to many of Taha Hussein’s writings marked (with Al-Mutanabbi), and he accused Taha Hussein of stealing a book named (Al-Mutanabbi) by Mahmoud Shaker. Then he discussed in a group of articles the curriculum and how the approach to literature taste was not Shakir's invention or creation out of nowhere but embedded in the heritage of Arabic language and literature. He only drew its features, outlined its dimensions, and worshiped its path for everyone who wanted to walk on it. Muhammad Abi Musa was one of his eminent students that followed all these debates, had a clear impact on Moses’ thought and his approach to criticism and art after that, which was not far from what Mahmoud Shaker planned.